The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1111/evj.13289
|View full text |Cite
|
Sign up to set email alerts
|

BEVA primary care clinical guidelines: Wound management in the horse

Abstract: Background: There are currently no evidence summaries on wounds in the horse. Objectives: To develop evidence-based guidelines on wound management in the horse. Study design: Evidence review using the GRADE framework. Methods: Research questions were proposed by a panel of veterinarians, and developed into PICO format. Evidence in the veterinary literature was evaluated using the GRADE evidence-to-decision framework. Searches for human evidence summaries were conducted in the NICE, Cochrane and JBI databases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 41 publications
0
19
0
2
Order By: Relevance
“…The recently published BEVA guidelines for evidence-based medicine on equine wound healing clearly pointed out the overall poor evidence in wound healing studies (Freeman et al, 2020). To establish practical evidence-based guidelines, clear parameters that can be objectively scored are a prerequisite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recently published BEVA guidelines for evidence-based medicine on equine wound healing clearly pointed out the overall poor evidence in wound healing studies (Freeman et al, 2020). To establish practical evidence-based guidelines, clear parameters that can be objectively scored are a prerequisite.…”
Section: Discussionmentioning
confidence: 99%
“…The delay or failure to heal is multifactorial and probably related to disruption of the delicate balance of growth factors and inflammatory mediators (Knottenbelt, 1997;Theoret and Wilmink, 2016). A recent systematic literature study on equine wound management revealed that peer-reviewed literature provides insufficient data to establish evidence-based wound management recommendations (Freeman et al, 2020). Currently, practitioners rely on textbooks paired with their personal experience to determine the strategy for wound treatment (Knottenbelt, 2003;Hendrickson, 2004;Theoret and Schumacher, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review concluded that there is no evidence to recommend any topical therapy over another for treating biofilm in chronic wounds in humans [124]. Further, the British Equine Veterinary Association (BEVA) recently (2021) published a review article on primary care clinical guidelines for equine wound management [125], however no guidance on topical treatment of equine wounds is provided as the evidence is lacking. No studies have investigated the effect of any treatment on biofilms in equine wounds.…”
Section: Treatment Of Biofilm In Woundsmentioning
confidence: 99%
“…They are considered the highest level of evidence and are used to inform and guide national and international medical health care policies and guidelines. 9,12,13 The challenge in veterinary medicine compared with human medicine is that our data sets are much smaller, and study approaches and methodologies often vary significantly which means that it may not be possible to combine or collate data sets. 2 A logical first step therefore may be to review the evidence/ publications that are currently available, organise these into broader areas or categories, and identify any suitable bodies of evidence for a systematic review.…”
mentioning
confidence: 99%
“…All have their place in evidence-based clinical practice and bring different advantages and disadvantages (Table 1). As increasing numbers of evidence syntheses are published, these will increase our understanding of the current bodies of evidence in veterinary medicine, 7,8 inform how we use evidence in our practices and policies 12,13 and shape how we develop future research to generate the best evidence going forwards. 15,16 Equine Veterinary Journal is publishing increasing numbers of papers describing evidence synthesis.…”
mentioning
confidence: 99%